Pengembangan E-Modul Ajar IPA Berbasis Inquiry Learning untuk Meningkatkan HOTS Literasi Sains Siswa Sekolah Dasar: Development of an Inquiry Learning-Based Science Teaching E-Module to Improve HOTS Science Literacy of Elementary School Students - Sartika Sari Sinaga; Retno Dwi Suyanti; Sumarno Sumarno (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Conditions at SDN 104212 Patumbak District indicate that student learning outcomes in science subjects still rely on conventional science learning processes, teacher-centered instruction, and interactive teaching materials, such as inadequate e-learning modules, and assessment instruments that are not yet oriented towards higher-order thinking skills (HOTS). This results in students having fewer opportunities to be actively involved and to improve their science literacy skills. This study uses a research and development method (Research and Development) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation, and, at the effectiveness test stage, uses a one-group pretest-posttest design. The results of the study show: (1) The developed e-learning module has an average feasibility percentage of 88% in the very feasible category; (2) The developed e-learning module is stated to be practical based on the results of the student response questionnaire with an average percentage of 92% which means the e-module is easy to use; (3) The e-learning module was declared effective with an average student pretest score of 57.84 with a minimum score of 44 and a maximum score of 69, and a standard deviation of 85.64 with a minimum score of 75 and a maximum score of 94, and a standard deviation of 5.844. Based on the results of this study, it can be concluded that student learning outcomes improved after using the inquiry-based science e-learning module. Furthermore, the results of the paired-samples t-test showed a p-value < 0.001, indicating a significant difference between the students' pretest and posttest results. Thus, H_0 was rejected, and H_a was accepted.